THE EFFECT OF WHOLESOME SCATTERING GAME TOWARDS STUDENTS’ ABILITY IN WRITING DESCRIPTIVE TEXT AT SMPN 35 MAKASSAR - Sardi Sardi (Publikasi dan UKI Press UKI Toraja., 2022)
The aim of this study is to describe the way students’ writing ability of the third-year students improved by using Wholesome Scattering Game of SMP Negeri 35 Makassar. The study employed Experiment Class. Where the subject consisted of 30 students who taken from class IX-1 of the third-year students of SMP Negeri 35 Makassar. The instrument of this research was writing test. The data were collected in pre-test and post-Test. The result indicates that the mean score in pre-test of experiment class was 55 and posttest was 85,83 It shows that used of Wholesome Scattering Game as a medium has effect on students’ writing paragraph at SMP Negeri 35 Makassar